PROBLEMS AND IMPACT OF BULLYING IN THE SCHOOL ENVIRONMENT - Atur, Theresa (LP3MKIL, 2024)
Adolescence is a critical developmental phase marked by significant physical, emotional, social, and psychological changes. This study explores the role of strategy and guidance counsellors in supporting adolescents, particularly in addressing bullying in schools. Strategy, defined as a planned pattern of actions, is essential for fostering positive outcomes in educational settings. Guidance counsellors, with specialized knowledge in counselling, are crucial in providing support and mitigating conflicts. Bullying, a form of juvenile delinquency involving repetitive, intentional harm by someone with greater power, poses severe risks to adolescents' well-being. Understanding bullying dynamics and implementing strategic interventions can help create a supportive environment for adolescents. This study underscores the importance of a coordinated approach involving educators, counsellors, parents, and the community to address the challenges of adolescence, promote healthy development, and ensure the safety and well-being of students.